Emotional Apathy and Its Relationship with Procrastinating Personality Among Students of Colleges of Education in Iraq - Khadir, Rusul Salman; Ali, Noor Jabbar (Journal of Posthumanism, 2025)
This study examines emotional apathy and its relationship with procrastinating personality among students of Colleges of Education in Iraq. It explores differences in emotional apathy and procrastination based on gender (male–female), specialization (scientific–humanities), and university affiliation (Basra, Mosul, and Diyala). The findings indicate that students exhibit high levels of emotional apathy due to stress and conflict, leading to indifference toward their surroundings. This apathy is more prevalent among males, scientific-specialization students, and those in Basra. Similarly, procrastination is common due to fear of failure, with higher levels among the same groups. Furthermore, a positive correlation exists between emotional apathy and procrastination, suggesting that as emotional detachment increases, so does procrastination. These results highlight the psychological challenges faced by students and emphasize the need for interventions to enhance motivation and reduce academic procrastination.